IMPROVING STUDENTS’ ENGLISH SPEAKING SKILL BY USING DRAMA (A Classroom Action Research at the Second Grade of SMA Muhammadiyah 1 Surakarta in 2010/2011 Academic Year) - Chandra, Aqlisty Nia (2011)
This research is conducted to know whether drama can improve students‟ speaking ability. It also aims to give general description about the implementation of drama in the classroom and about the things happening in the class when it is implemented. The objective of this research is determined after identifying the problems during pre-observation in class XI IPS 5 of SMA Muhammadiyah 1 Surakarta, interviewing the students and the English teacher of that class, and investigating the teacher about her note dealing with the students‟ score in daily evaluation especially speaking subject. The method used in this research is action research. The research is conducted in three cycles to the second grade students of SMA Muhammadiyah 1 Surakarta. The researcher teaches speaking English using drama technique. The research data are collected by using techniques of qualitative and quantitative data collection which include: observation, interview, documentation, pre-test and post-test. This classroom action research concerns with solving the problems by identifying them, planning, implementing, and observing the action, reflecting the result of the observation, and revising the plan for the following steps. The result of the research shows that drama can improve students‟ speaking ability. Besides, their test achievement during the research is better than their score in the teacher‟s note before the actions are implemented. The students‟ mean score before the action is 45.05. It improves up to 54.67 in the first cycle, 66.10 in the second cycle, and improves again up to 75.81 in the third cycle.